Oxidative stress index as a biochemical parameter in major depressive disorder - Gupta, Soma; Kunti, Sanjoy; Chatterjee, Sharmistha; Dutta, Suvendu; Nath, Saswati; Das, Harendra Nath (Asian Journal of Medical Sciences, 2016)
Background: Oxidative stress is considered to be involved in pathogenesis of different diseases including Major Depressive Disorder (MDD). In laboratory, this can be measured by a biochemical parameter called Oxidative stress Index (OSI), which can be calculated as the ratio percentage of Total peroxide to the total anti-oxidant potential. Aims and Objectives: This study was undertaken to determine OSI in MDD and healthy control and to find out whether any significant difference exists among the mean values of OSI in MDD and healthy controls. It was also aimed to find out whether OSI can be correlated with the severity of MDD. The validity of OSI as a biochemical parameter to diagnose MDD was also evaluated. Materials and Methods: In this study OSI was determined in 101 cases of Major Depressive Disorder (MDD) along with 106 age and sex matched controls by measuring Total Peroxides (TP) and Total Antioxidant Capacity (TAC). TP was measured by (FOX 2) method and TAC was measured by The Ferric Reducing Ability of Plasma (FRAP) method. The correlation of OSI & severity of depression was assessed by Spearman rank Correlation test. ROC curve was used for determining the validity of OSI for diagnosis of Depression. Result: Significant increase in OSI was observed in MDD (2.33 + 0.457) when compared to healthy controls (1.311 + 0.352). The increase was also found to be associated with severity of MDD (Spearman coefficient of rank correlation, rho = 0.289). The diagnostic ability of OSI was evaluated by ROC curve, which showed Area under curve as 0.96. The optimal cut off value of OSI was found to be 1.83, with 87.13% sensitivity and 92.45% specificity. Conclusion: Oxidative stress may play a role in pathogenesis of MDD as indicated by measuring OSI. This parameter is found to be significantly associated with severity of disease. The diagnostic ability of OSI for MDD is quite satisfactory. However, further study is needed to validate this finding. Asian Journal of Medical Sciences Vol.7(5) 2016 31-35